(3jhejGJ YGe GdWGYhf (B/s - (3Ojah, OGfjGd,s 1661-1731; (3GdLhdGfj, aGjR cGed EHQGgjes; (3NQjS, CMeO,s 1970-; (3CHh GdgjLGA, fGUQ eUWais; (3Ojah, OGfjGd,s 1661-1731. ((3CHh XHj (B:s (3OGFQI GdKbGaI hGdSjGMI, eQcR CHh XHj ddZI GdYQHjI, eTQhY cdeIs, 2021)
(3jYO cJGH (B"(3jhejGJ YGe GdWGYhf(B" (3OdjdG EQTGOjG ddMcheGJ ceG GdCaQGO aj SjGb ehGLgI GdChHFI, ShGA ef LgI Sf GdbhGfjf hGdfXe hGdELQGAGJ GdQbGHjI hGdYbGHjI, Ch ef LgI GdSdhcGJ GdGLJeGYjI, YQVG hJaSjQG hfbOG(B. (3hjDQN GdcJGH dhHGA (B"(3GdWGYhf(B" (3GdPj GLJGM EfLdJQG YGe (B1665(3, hChOi HMjGI CcKQ ef (B97000 (3TNU, heG UMHg ef ELQGAGJ, cGdYRd GdefRdj, hGdMLQ GdUMj, hEfTGA eTGa ddCeQGV GdhHGFjI, hGdJHGYO GdGLJeGYj, hGdGMJjGWGJ GdJLGQjI, hJbfjf GdJQMGd hGdJfbd, hGdJYbje(B. (3hJTHg (S0(3GdjhejGJ(S1(3, ef MjK GdTcd, GdQhGjI GdJGQjNjI, dcfgG PGJ EjbGY JSLjdj jQUO eSGQGJ GdhHGA hBKGQg, hjSYi Edi JaSjQ Sdhcg, HCSdhH jJQGhM Hjf GdbU hGdJhKjb, hGfWHGYjI JMPh MPh GdHQgfI GdYdejI aj ZjQ bVjI(B. (3hdYd CHQR eG dGMXg (S0(3Ojah(S1 (3Cf WGYhf dfOf GdVGQj de jSdc eSGQG NWjG, Hd efMfi LjHjG PG JhRY efGWbj, hCf VQGhJg bO JHGjfJ aj eHJOFg YeG BdJ Edjg d`eG HdZ PQhJg, Ke GfNaVJ M`OI aJc`g, hEPGc GJSY fWGb`g, aGQJaY`J CY`OGO Gd`eU`GHjf Hg, MJ`i ChT`c Ydi GdGfMSGQ, hef Ke NeO(B. (3hbO UOQ GdcJGH, Chd eQI, YGe (B1722.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3Ojah, OGfjGd,s -- 1661-1731 -- (3jhejGJs; (3GdWGYhfs -- (3EfLdJQGs -- (3JGQjNs -- (3bQf (B17s -- (3eQhjGJ TNUjIs